Semi–group of conformal mappings of the upper half–plane onto itself with the hydrodynamic normalization at infinity - Горяйнов, В. В.; Ba, I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The objects of this study are holomorphic functions, univalent in the upper half–plane, which are complex potentials of infinitely deep flows over a flat bottom with unperturbed flow at infinity. The semigroup of all such functions is determined and its infinitesimal description given.